The demineralization of Sardinella gibbosa scales using hydrochloric acid and high-pressure carbon dioxide - Saleah, Faisa; Netramai, Siriyupa; Kijchavengkul, Thitisilp; Wipatanawin, Angkana; Rosales, Czarina Kristine (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
This research aimed to investigate and compare the demineralization ofgoldstripe sardinella (GS; Sardinella gibbosa) scales, a major by-product inthe canned fish industry prevalent in East Africa and Southeast Asia, particularlyThailand. The study focused on conventional and alternative demineralizationmethods, assessing the yield and quality of the demineralized scales. Afterremoving minerals, fish scales have potential value as an alternative sourceof collagen and gelatin. For the strong acid treatment using hydrochloricacid (HCl), the effects of HCl concentrations (0.2-1.5 M) and treatmenttimes (30-120 min) on demineralization efficiency were assessed. The resultsfrom RSM indicated that HCl concentration was the only treatment factorthat significantly affected demineralization yield, HCl concentrations at orabove 0.82 M gave a demineralization efficiency of e” 99%, independent oftreatment time (P 0.0001). A preliminary investigation into high-pressurecarbon dioxide (HPCD) treatment of GS scales (at 10 bar for 1 to 4 h)showed comparatively lower demineralization efficiency. Within the studiedparameters, the highest demineralization efficiencies for both methods were99.89±0.06 and 16.13±1.92%, respectively. SEM images and EDX analysisconfirmed the complete removal of minerals (primarily Ca and P) after HCltreatment using HCl 0.85 M for 30 min. Conversely, HPCD-treated scalesexhibited altered structure and physical damage.